The role of traditional and modern media in the lives of children and young people - Ljajić, Samir H. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
In contemporary society, media are an integral and indispensable part of the lives of young people. Young people get acquainted with the media very early, at an early age, in family conditions, when they come in contact with television, press or the new technologies used by their parents. In this period, children's most interesting media content, such as children's programs, educational programs, cartoons, films that are interesting to children, include films with animals, then music, fairy tales, picture books and computer games that are becoming more and more relevant. As children grow up, they expand the diverse range of the media they use. At school age, they are still very much inclined towards television and the various content that it offers, and in recent times, young people have been devoting special attention to computers, tablets and mobile phones. During adolescence, the connection between youth and the media is becoming even more pronounced, so in the period of high school, young people spend most of their free time with the media. It is known that the media have an undeniable influence on the development of personality, during the entire growing up period, which gives even more significance to the role of the media, both traditional and modern ones
Keywords: personality; adolescents; children; contemporary media; traditional media